2019
DOI: 10.3390/coatings9100595
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Testing of a Novel Sprayable Crosslinked Edible Coating Based on Salmon Gelatin

Abstract: The aim of this study was to develop and characterize a sprayable edible coating using salmon gelatin (SG) and its stabilization by photopolymerization using riboflavin (Rf). Suspensions of SG with Rf at pH values of 5.0 and 8.5 were exposed for 2 min to visible light (VL) and ultraviolet (UV) light and further characterized to determine structural changes of the different gelatin formulations. Rheology analysis showed that at pH 5, the loss modulus (G’’) was higher that the storage modulus (G’) for crosslinke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Three samples were selected in each experiment and the mean values of CA were reported. In general, gelatin has hydrophilic properties, and it displays excellent wettability in comparison with other polymers [ 46 , 47 , 48 , 49 ]. As can be seen in Table 3 , the gelatin nanofiber scaffold had a mean CA of 20.65°.…”
Section: Resultsmentioning
confidence: 99%
“…Three samples were selected in each experiment and the mean values of CA were reported. In general, gelatin has hydrophilic properties, and it displays excellent wettability in comparison with other polymers [ 46 , 47 , 48 , 49 ]. As can be seen in Table 3 , the gelatin nanofiber scaffold had a mean CA of 20.65°.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanical behavior is interesting since low viscosity and low gelling temperature SG could provide a technological advantage over mammal gelatins at high concentration since it retains a suitable viscosity for applications relevant to foods, pharma, and biomedicine among other application [ 8 , 10 , 53 ]. For example, a novel sprayable photo-sensitive SG-based coating has been recently described by Char et al [ 4 ], where the low viscosity and low gelling temperature of SG allowed the application of this coating under low temperature conditions normally used by the food industry (T < 6 °C), and therefore easing the adoption of this technology by the industry. On the other hand, Zaupa et al [ 10 ] have reported the technical advantages of SG for use with biofabrication purposes over mammal gelatin, where a combination of low gelling temperature, higher molecular mobility (relaxation times T2 by NMR), and lower capacity of SG to thermal inducing random coil to triple helix transformation upon cooling (circular dicroism), resulted in important advantages for tuning the rate of extra cellular matrix remodeling, which is relevant for wound healing treatments and tissue engineering applications.…”
Section: Resultsmentioning
confidence: 99%
“…Fish skin is known to be a good source of collagen and gelatin [ 1 , 2 , 3 ]. Gelatin, a partially hydrolyzed form of the fibrillar protein of collagen, can be used for the design of multifunctional biomaterials and composites with interesting applications in the food [ 4 ], pharmaceutical, and biomedical industries [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riboflavin was used to eliminate TEMED, as the oxidative system may exhibit toxicity [38]. The addition of riboflavin also formed a network, which could be a sign that crosslinking could be mediated by visible light [39]. Even though, the most homogeneous materials were produced by Irgacure 2959 (Figure 8).…”
Section: Crosslinking Of Ha-udamentioning
confidence: 99%